(3Shb GdQbjbs - (3eMeO Hf eMeO Hf eMeO Hf GdMSf GdLPGej GdaGQbj GdeUQj, GHf fHGJg , LeGd GdOjf CHh HcQ,J (B768 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO Gddg Ydi eG efM ef Qbjb Gdbhd hLRdg agPg fHPg ef CYeGd TYQi hCYeGd hdOi ESeGYjd SejJgG Shb GdQbjb s
(3BNQgG (B:s
(3hCfJ hGUH hUa PG GdUHi Je GdcdGe YfOg adJfUH hGJHY GdEZRGd eOMkG eYLHG fMh GdbGVi GdePHG s
(3OjhGf TYQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B38 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B273 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B164s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs